Possible Role of Nitric Oxide in Anxiety Following Transient Cerebral Ischemia in Mice - Mihoko N. Nakashima; Ken-ichi Ajiki; Kenichiro Nakashima; Masakatsu Takahashi (Elsevier, 2003)
The possible role of nitric oxide (NO) in anxiety following transient cerebral ischemia by a 10-min bilateral carotid occlusion was examined in mice. Two days after the ischemia, mice showed a significant decrease in time spent on the open arms in the elevated plus-maze test; and likewise, they showed shortened social interaction time in the social interaction test, suggesting the induction of anxiety. Such anxiety behavior, however, was diminished 7 days after the treatment in both tests. A nonselective nitric oxide synthase (NOS) inhibitor, Nw-nitro-L-arginine methyl ester (L-NAME), and a selective inducible NOS (iNOS) inhibitor, S-ethylisothiourea (EIT), given twice after reperfusion, produced an anxiolytic effect in the elevated plus-maze test 2 days after the ischemia, while only the former produced antianxiety in the social interaction test. A relatively selective neuronal NOS (nNOS) inhibitor, 7-nitroindazole (7-NI), failed to decrease the level of anxiety in both tests. These results suggest that the production of NO participates in the anxiogenic behavior by the ischemia. Furthermore, NO generated by endothelial NOS (eNOS) or eNOS with iNOS, with no involvement of nNOS, plays an important role in the anxiety induced by the ischemia. Thus, we conclude that 10-min bilateral carotid occlusion provides a useful exploratory animal model for anxiety following transient cerebral ischemia.